# I need help simplifying this radical expression: 3√12 + √27 - 2√20 Thanks in advance!

### 2 Answers | Add Yours

`3sqrt(12)+sqrt(27)-2sqrt(20)=3sqrt(4xx3)+sqrt(3^3)-2sqrt(5xx4)=`

`3sqrt(2^2xx3)+sqrt(3^2xx3)-2sqrt(5xx2^2)=` `3xx2sqrt(3)+3sqrt(3)-2xx2sqrt(5)=`

`=6sqrt(3)+3sqrt(3)-4sqrt(5)=9sqrt(3)-4sqrt(5)`

Given: `3sqrt(12)+sqrt(27)-2sqrt(20)`

Simplify the roots. When selecting factors, choose one factor that is a perfect square.

`=3sqrt(4)sqrt(3)+sqrt(9)sqrt(3)-2sqrt(4)sqrt(5)`

`=3(2)sqrt(3)+3sqrt(3)-2(2)sqrt(5)`

`=6sqrt(3)+3sqrt(3)-4sqrt(5)``

Combine like terms.

`=9sqrt(3)-4sqrt(5)`

The answer is: `9sqrt(3)-4sqrt(5)`